Hepatic stellate cell‐released CXCL1 aggravates HCC malignant behaviors through the MIR4435‐2HG/miR‐506‐3p/TGFB1 axis. Issue 2 (4th December 2022) - Li, Shaling; Hu, Xingwang; Yu, Songman; Yi, Panpan; Chen, Ruochan; Huang, Zebing; Huang, Yan; Huang, Yun; Zhou, Rongrong; Fan, Xuegong
Abstract: Hepatic stellate cell (HSC) activation is a critical event in the development of hepatic fibrosis and hepatocellular carcinoma (HCC). By the release of soluble cytokines, chemokines, and chemotaxis, HSCs affect HCC cell phenotypes through a complex tumor microenvironment. In this study, weighted gene co‐expression network analysis (WGCNA) was used to identify the TGF‐β signaling pathway as a key signaling pathway in Hep3B cells cultured in HSC conditioned medium. MIR4435‐2HG is a hub lncRNA associated with the TGF‐β signaling pathway and HSC activation. HSC‐condition medium (CM) culture induced HCC cell malignant behaviors, which were partially reversed by MIR4435‐2HG silencing. miR‐506‐3p directly bound to MIR4435‐2HG and the 3′UTR of TGFB1. Similarly, overexpression of miR‐506‐3p also attenuated HSC‐CM‐induced malignant behavior of HCC cells. In HSC‐CM cultured HCC cells, the effects of MIR4435‐2HG knockdown on TGFB1 expression and HCC cell phenotypes were partially reversed by miR‐506‐3p inhibition. HSCs affected HCC cell phenotypes by releasing CXCL1. In an orthotopic xenotransplanted tumor model of HCC cells plus HSCs in mice, CXCR2 knockdown in HCC cells significantly inhibited tumorigenesis, which was partially reversed by MIR4435‐2HG overexpression in HCC cells. In HCC tissue samples, the levels of CXCL1, TGF‐β1, and MIR4435‐2HG were upregulated, while miR‐506‐3p expression was downregulated. In conclusion, HSC‐released CXCL1 aggravated HCC cell malignant behaviors through the MIR4435‐2HG/miR‐506‐3p/TGFB1 axis. In addition to CXCL1, the MIR4435‐2HG/miR‐506‐3p/TGFB1 axis might also be the underlying target for HCC therapy. Abstract : 1. MIR4435‐2HG silencing inhibits HSC‐CM‐induced HCC cell malignant behaviors 2. miR‐506‐3p directly targets MIR4435‐2HG and TGFB1 3'UTR 3. miR‐506‐3p overexpression attenuates the effects of HSC‐CM on HCC cells 4. MIR4435‐2HG mediates HSC‐CM effects on HCC cells through miR‐506‐3p and downstream TGFB1